2014
DOI: 10.2105/ajph.2014.301951
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities in Telephone-Based Treatment of Tobacco Dependence

Abstract: Although quitlines often increase access to treatment for some lower SES smokers, significant socioeconomic disparities in treatment outcomes raise questions about whether current approaches are contributing to tobacco-related socioeconomic health disparities. Strategies to improve treatment outcomes for lower SES smokers might include novel methods to address multiple factors associated with socioeconomic disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…For example, those with higher SES have consistently achieved greater rates of long term abstinence compared to those with lower SES following participation in tobacco dependence treatment programs. 67, 75 Therefore, it is not surprising that alternative or enhanced treatments have been suggested for health conditions 19, 39, 74 including LBP 9, 17 that specifically consider the circumstances of patients with low SES. Previous suggestions have also indicated that self-management approaches, particularly those incorporating cognitive behavioral principles, may be more appropriate for higher SES individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, those with higher SES have consistently achieved greater rates of long term abstinence compared to those with lower SES following participation in tobacco dependence treatment programs. 67, 75 Therefore, it is not surprising that alternative or enhanced treatments have been suggested for health conditions 19, 39, 74 including LBP 9, 17 that specifically consider the circumstances of patients with low SES. Previous suggestions have also indicated that self-management approaches, particularly those incorporating cognitive behavioral principles, may be more appropriate for higher SES individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Lower SES groups smoke at 3 to 4 times the prevalence of higher SES groups making tobacco use one of the greatest contributors to health disparities (BRFSS - Centers for Disease Control and Prevention, 2012). While motivation to quit and attempts to quit show no socioeconomic gradient, lower SES groups are less likely to successfully quit once they begin smoking even when provided with a variety of treatments and treatment modalities (Agrawal et al, 2008, Barbeau, Krieger & Soobader, 2004, Centers for Disease Control and Prevention, 2005, Fagan et al, 2007, Ferguson et al, 2005, Kotz & West, 2009, Reid et al, 2010, Trinidad et al, 2011, Wetter et al, 2005a, Sheffer et al, 2012b, Varghese et al, 2014, Kandel, Griesler & Schaffran, 2009). At present, tobacco use is the leading contributor to health disparities in the US and elsewhere, and unlike many other health disparities, tobacco-related cancer health disparities actually appear to be increasing (Jha et al, 2006, Kanjilal et al, 2006, Mokdad et al, 2004).…”
Section: What Is the Extent Of The Ses Gradient Among Important Healtmentioning
confidence: 99%
“…This manual-driven, multicomponent cognitive behavioral treatment for tobacco dependence has been delivered in multiple modalities (i.e., group, individual, and telephone), used in numerous studies [17-20,56-59], and is considered comprehensive, well-established, and consistent with the Public Health Service Clinical Practice Guideline [22]. When delivered in the group treatment modality, the treatment consists of 6 weekly closed-group 60-minute sessions with 5-10 participants.…”
Section: Methodsmentioning
confidence: 99%
“…The research team reviewed conceptual models of socioeconomic and tobacco use disparities [12,25,28,30-35,60] and the findings associated with disparities in tobacco dependence treatment outcomes [17,18,20,58,61,62]. We identified eight modifiable factors associated with socioeconomic disparities that were prominent in both theoretical frameworks and treatment outcome studies: stress and stress management, negative affect regulation, smoking in response to negative affect, delay discounting, locus of control, impulsiveness, smoking policies in the home, and treatment utilization (e.g., medication and session attendance).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation